2020
DOI: 10.1021/acs.analchem.0c01187
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Bioanalytical Methods for the Comprehensive Pharmacokinetic and Catabolic Assessment of MEDI3726, an Anti-Prostate-Specific Membrane Antigen Pyrrolobenzodiazepine Antibody–Drug Conjugate

Abstract: Complex biotherapeutic modalities, such as antibody-drug conjugates (ADC), present significant challenges for the comprehensive bioanalytical characterization of their pharmacokinetics (PK) and catabolism in both preclinical and clinical settings. Thus, the bioanalytical strategy for ADCs must be designed to address the specific structural elements of the protein scaffold, linker, and warhead. A typical bioanalytical strategy for ADCs involves quantification of the Total ADC, Total IgG, and Free Warhead concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…ADCs are complex biotherapeutic modalities that require sophisticated bioanalytical methods to properly interrogate their PK and catabolism (49,61). To enable quantitative analysis of changes in DAR over time for MEDI426 and to assess the impact that deacetylation would have on the tubulysin warhead, we employed sophisticated, novel, DAR-sensitive, bioanalytical methods for the assessment of MEDI4276 PK (50).…”
Section: Discussionmentioning
confidence: 99%
“…ADCs are complex biotherapeutic modalities that require sophisticated bioanalytical methods to properly interrogate their PK and catabolism (49,61). To enable quantitative analysis of changes in DAR over time for MEDI426 and to assess the impact that deacetylation would have on the tubulysin warhead, we employed sophisticated, novel, DAR-sensitive, bioanalytical methods for the assessment of MEDI4276 PK (50).…”
Section: Discussionmentioning
confidence: 99%
“…Antibody-drug conjugates (ADC) present significant bioanalytical challenges for ensuring comprehensive PK characterization. In a case study, multiple hybrid assays were developed in order to appropriately characterize the PK properties of a unique ADC, ultimately measuring at least 14 unique species/catabolites [27]. In another case study, this technique was used for ADA impact assessments [28], where hybrid assays were developed to confirm the impact on the PK by ADA and to deconvolute the ADA binding domain.…”
Section: Discussion Topics and Consolidated Questions Collected From The Global Bioanalytical Communitymentioning
confidence: 99%
“…After proving TARSC analysis enables ADC catabolism studies in lysosomes, we next asked whether TARSC is applicable to examine the active payloads released from ADCs in intact cells where multiple crucial biological processes including antigen‒antibody binding, intracellular internalization, trafficking and lysosomal degradation can be reflected 12 , 30 . We found that lys-MCC-DM1 did not show dose-dependent increase with the administered concentrations of T-DM1, whereas DM1 increased with the ramped administered concentrations.…”
Section: Discussionmentioning
confidence: 99%